2021
DOI: 10.21203/rs.3.rs-419113/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A step Towards Environmental Mitigation In South Africa: Does Trade Liberalisation Really Matter? Fresh Evidence From A Novel Dynamic ARDL Simulations Approach

Abstract: This study revisits the trade-CO2 emissions nexus for South Africa over the period 1960–2016. Our strategy is distinctively different from previous works in the following dimensions: we employ the recently developed novel dynamic autoregressive distributed lag (ARDL) simulations framework to examine the negative and positive changes in trade openness, technological innovation, industrial growth, energy consumption, foreign direct investment, technique effect, and scale effect on CO2 emissions. Second, we use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…The minimum requirement for innovation is that the production process, marketing approach must be new or highly developed by the company. In this context, some empirical works have found that technological innovation improves the quality of the environment (Udeagha and Ngepah, 2021a;Udeagha and Ngepah, 2021b). However, some studies have concluded that technological innovations have added to the growing levels of environmental degradation (Atsu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The minimum requirement for innovation is that the production process, marketing approach must be new or highly developed by the company. In this context, some empirical works have found that technological innovation improves the quality of the environment (Udeagha and Ngepah, 2021a;Udeagha and Ngepah, 2021b). However, some studies have concluded that technological innovations have added to the growing levels of environmental degradation (Atsu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As income grows, the scale effect (economic growth) adds to increased environmental degradation; however, the technique effect lessens environmental decay as much stricter environmental regulations are enacted to improve environmental quality (Ling et al 2015 ; Cole and Elliott 2003 ; Udeagha and Ngepah 2021a ). As a result, the validity of the EKC hypothesis requires that and .…”
Section: Methodsmentioning
confidence: 99%
“…Global warming and climate change are currently among the world's most disputed and concerning topics, and there is growing agreement that these concerns must be addressed immediately (Udeagha and Ngepah 2021a , 2021b ). In recent years, the world has seen a rapid increase in greenhouse gas (GHG) emissions, such as carbon dioxide (CO 2 ) emissions, which are the driving forces for climate change resulting from internal changes within the climate system, from 22 billion tonnes in 1990 to over 34 billion tonnes emitted annually (World Bank 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nation is one of the top seven most decentralized nations in the world, with a fiscal decentralization ratio that is higher on average than 58% globally in 2018 and higher than the global average (Shan et al, 2021). Third, South Africa can accomplish the Sustainable Development Goals (SDGs) to advance socio‐political, environmental, and economic goals (Udeagha & Ngepah, 2021b). These factors make it possible to look at how uncertainty in economic policy, fiscal decentralization, and green innovation all interact to affect environmental quality in South Africa.…”
Section: Introductionmentioning
confidence: 99%